The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1515/tnsci-2020-0204
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells overexpressing hepatocyte growth factor ameliorate hypoxic–ischemic brain damage in neonatal rats

Abstract: Objectives Hypoxic–ischemic brain damage (HIBD) is a major cause of brain injury in neonates. Bone marrow mesenchymal stem cells (BMSCs) show therapeutic potential for HIBD, and genetic modification may enhance their neuroprotective effects. The goal of this study was to investigate the neuroprotective effects of hepatocyte growth factor (HGF)-overexpressing BMSCs (BMSCs-HGF) against HIBD and their underlying mechanisms. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The gerbils after modeling had severe cerebral ischemia and exhibited significant neurological deficits such as facial paralysis, limb weakness, and abnormal movement. In this study, permanent ligation of the right carotid artery in gerbils was used as modeling method, prolonged ischemia time could also lead to gradual ischemia of the contralateral brain [ 42 , 43 ]. This discovery suggested that for sudden CIS, timely treatment should be taken to avoid worsening of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The gerbils after modeling had severe cerebral ischemia and exhibited significant neurological deficits such as facial paralysis, limb weakness, and abnormal movement. In this study, permanent ligation of the right carotid artery in gerbils was used as modeling method, prolonged ischemia time could also lead to gradual ischemia of the contralateral brain [ 42 , 43 ]. This discovery suggested that for sudden CIS, timely treatment should be taken to avoid worsening of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Even more surprising was the negative correlation we observed between OGD neuroprotection and HGF concentration, HGF having recently been indicated as a key factor in preventing neuronal death and promoting survival through pro-angiogenic, anti-inflammatory, and immune-modulatory mechanisms in vivo [ 62 ]. Bone marrow-derived MSCs transfected with HGF also protected neurons against OGD-induced apoptosis [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%